Spatial Variations in Crustal and Mantle Anisotropy Across the North American‐Caribbean Boundary on Haiti. Issue 6 (30th May 2020) - Possee, Daniel; Keir, Derek; Harmon, Nicholas; Rychert, Catherine; Eakin, Caroline; Rolandone, Frédérique; Leroy, Sylvie; Corbeau, Jordane; Stuart, Graham; Boisson, Dominique; Momplaisir, Roberte; Prépetit, Claude
Abstract: Haiti, on the island of Hispaniola, is situated across the North American‐Caribbean plate boundary at the transition point between oblique subduction in the east and a transform plate boundary in the west. Here we use shear wave splitting measurements from S waves of local (0–50 km) and intermediate depth (50–150 km) earthquakes as well as SK(K)S phases from teleseismic earthquakes to ascertain good spatial and vertical resolution of the azimuthal anisotropic structure. This allows us to place new constraints on the pattern of deformation in the crust and mantle beneath this transitional region. SK(K)S results are dominated by plate boundary parallel (E‐W) fast directions with ~1.9 s delay times, indicating subslab trench parallel mantle flow is continuing westward along the plate boundary. Intermediate depth earthquakes originating within the subducting North American plate show a mean fast polarization direction of 065° and delay time of 0.46 s, subparallel to the relative plate motion between the Caribbean and North American plates (070°). We suggest a basal shear zone within the lower ductile crust and upper lithospheric mantle as being a potential major source of anisotropy above the subducting slab. Upper crustal anisotropy is isolated using shear wave splitting measurements on local seismicity, which show consistent delay times on the order of 0.2 s. The fast polarization directions indicate that the crustal anisotropy is controlled by the fault networks in close proximity to the major strike‐slip faults, which bisect the north and south of Haiti, and by the regional stress field where faulting is less pervasive. Key Points: Multiple sources of anisotropy exist beneath Haiti at the transition from oblique subduction to oblique collision along the plate boundary Mantle anisotropy appears caused by subslab trench‐parallel mantle flow and a possible thin lithospheric shear zone Crustal anisotropy is associated with both the orientation of fault structures and the orientation of the regional stress field